2018
DOI: 10.1136/annrheumdis-2017-212608
|View full text |Cite
|
Sign up to set email alerts
|

Open-label, multicentre, dose-escalating phase II clinical trial on the safety and efficacy of tadekinig alfa (IL-18BP) in adult-onset Still’s disease

Abstract: ObjectivesAdult-onset Still’s disease (AOSD) is a rare systemic autoinflammatory disease; its management is largely empirical. This is the first clinical study to determine if interleukin (IL)-18 inhibition, using the recombinant human IL-18 binding protein, tadekinig alfa, is a therapeutic option in AOSD.MethodsIn this phase II, open-label study, patients were ≥18 years with active AOSD plus fever or C reactive protein (CRP) levels ≥10 mg/L despite treatment with prednisone and/or conventional synthetic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
175
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 18 publications
3
175
0
3
Order By: Relevance
“…The data presented here may suggest that targeting IL-18 may be therapeutically beneficial, by preventing adaptive cell airway infiltration whilst maintaining a potent IL-1 response to infection (Gabay, Fautrel et al, 2018b); however NLRP3 activation has a protective role in animal models of induced colitis (Allen, TeKippe et al, 2010) which may run contrary to the expectation that reduced NLRP3 expression might reduce inflammation in the bowel. Furthermore, IL-18 has an epithelial protective role in promoting the repair of gut epithelium (Zaki, Vogel et al, 2010), and further ex vivo studies and in models of CF are required to fully elucidate the potential benefits or, indeed, hazards of IL-18 blockade (Gabay, Fautrel et al, 2018a). It is notable that inhibition of TLR4 signalling was the most effective means of blocking excessive NLRP3 activation in our study, suggesting that targeting this pathway may be a therapeutic option (avenue) to treat this condition.…”
Section: Discussionmentioning
confidence: 73%
“…The data presented here may suggest that targeting IL-18 may be therapeutically beneficial, by preventing adaptive cell airway infiltration whilst maintaining a potent IL-1 response to infection (Gabay, Fautrel et al, 2018b); however NLRP3 activation has a protective role in animal models of induced colitis (Allen, TeKippe et al, 2010) which may run contrary to the expectation that reduced NLRP3 expression might reduce inflammation in the bowel. Furthermore, IL-18 has an epithelial protective role in promoting the repair of gut epithelium (Zaki, Vogel et al, 2010), and further ex vivo studies and in models of CF are required to fully elucidate the potential benefits or, indeed, hazards of IL-18 blockade (Gabay, Fautrel et al, 2018a). It is notable that inhibition of TLR4 signalling was the most effective means of blocking excessive NLRP3 activation in our study, suggesting that targeting this pathway may be a therapeutic option (avenue) to treat this condition.…”
Section: Discussionmentioning
confidence: 73%
“…Physiopathological data may highlight the efficacy of IL-17 or IL-18 blockade in AOSD. A recent study showed that IL-18 inhibition using the recombinant human IL-18-binding protein tadekinig alpha is a therapeutic option in patients with AOSD in a phase 2 open-label trial [46]. IL-17 [47] and INF-γ [48] blockade have not been studied yet but should be in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that levels of ‘free’ and total IL‐18 are elevated in many sHLH patients, while it has recently been reported that levels of ‘free’ IL‐18 are also significantly elevated among patients with sJIA and AOSD . These observations provided a sound rationale for an investigation of recombinant IL‐18BP as a treatment for AOSD patients in a phase II study, which demonstrated that targeting IL‐18 represents an effective therapeutic strategy . Although the studies described above have clearly established a therapeutic benefit of targeting IL‐18 activity in human disease, it is as yet unclear whether these effects can completely be ascribed to the inhibition of its IFNγ inducing activity.…”
Section: Targeting Il‐18 In Human Diseasementioning
confidence: 99%